ASSESSING IRRIGATED WATER QUALITY BASED ON PHYSICOCHEMICAL PROPERTIES: CASE STUDY: JENEBERANG RIVER, TAKALAR REGENCY, SOUTH SULAWESI, INDONESIA - Muhammad Qayyum Hamka; Shiji Wang (Journal of Engineering, Electrical and Informatics, 2023)
In South Sulawesi's Takalar Regency, the Jeneberang River serves as irrigation water for neighboring areas. Several parameters, including electrical conductivity, pH, toxicity, soluble sodium, Sodium Adsorption Ratio (SAR), PI, MH, and Kelly's Ratio, were used to examine the development of water quality. The observation was conducted over three months in 2021: June (5 points), July (5 points), and August (5 points). The method for conducting physiochemical analyses was based on FAO and WHO guidelines. The study results suggest that the research locations' electrical conductivity meets the irrigation water quality standards. The nitrite concentration at the study locations ranged from 0.04 to 10.88 mg/L; thus, it was acceptable and below the standard limit level. The values of calcium and magnesium were 2.54-10.3 and 0.03 mg/L, respectively. The sodium concentration ranged between 4 and 7 mg/L. In addition, the potassium concentration in this study's water samples varied between 0.03 and 0.19 mg/L. Meanwhile, the SAR values range from 0.03 to 0.34 meq/L and are categorized as an excellent class. According Soluble Sodium Percentage standart water sample are categorized as excellent to eligible. KR, PI, and MH also indicate water sample in the suitable conditon for agricultural uses. The lead concentration at all sites was constant, 0.027 mg/L. It also happens for cadmium measurements, which show a value always the same each month, specifically 0.001 mg/L. Eventually, the analysis of cations and anions indicates that the type of water is magnesium bicarbonate. In addition, based on Kelly's Ratio data, the Jeneberang River is suitable for agricultural irrigation.